EFEKTIVITAS KERJA SAMA INTERPOL - GAATW DALAM MENANGANI PERDAGANGAN MANUSIA DI JEPANG - Ghiffari, Fadil Budi; Pattipelohy, Shary Charlotte (Journal of International Relations, 2019)
This study discusses how the effectiveness of Japan in handling human trafficking cases that occur with the assistance of INTERPOL which will then be assessed based on the standard indicators set by the GAATW (Global Alliance Against Traffic in Woman) as NGOs (Non Governmental Organizations) in assessing the case . In the issue of human trafficking, Japan is a country that has very complex problems related to the issue and also prostitution in its country. Japan is a destination country for women and children from East Asia, Southeast Asia, Eastern Europe, Russia and Latin America who make victims of Human Trafficking. Victims are often lured by false promises such as offering jobs as models, servants, hotel staff, and entertainers. Prostitution in Japan itself can no longer be dammed, it can even be said to be a natural thing there. There needs to be great awareness in the community, especially in Japan itself, so that the community plays an active role in eradicating trafficking to the maximum with cooperation between the government and the community. In the case of the majority of victims the women and children of this crime are included in Organized Crime which means that a crime is committed in a network that is organized and carried out in sophisticated ways because of the influence of advances in information technology. This weak public awareness is increasingly triggering Trafficking practices that will continue to develop. In this study the author explains with the theory of Liberalism Institutionalism which considers that the key focus of institutional liberalism is about the way in which institutions provide information for the state. In the end human trafficking in Japan has improved enough even though it cannot just disappear. However, the case has improved considerably and is not as prevalent before INTERPOL conducted research on human trafficking in Japan.